Bioethics: a comparative study of its concepts, issues and approaches - Hashi, Abdurezak Abdulahi (IIUM Press, 2015)
This book, Bioethics: A Comparative Study of its Concepts, Issues and Approaches, addresses moral and ethical issues related to contemporary biomedical and biotechnological practices. It also addresses the history and approaches, as well as, the scope of the field of bioethics. Besides illustrating the moral foundations, concepts and approaches of bioethics, this book elucidates the moral implications and issues of biomedical practices such as organ transplantation, contraception, abortion, euthanasia, cloning, artificial insemination and test tube babies.